Analisis Pengembalian Portofolio Investasi Perusahaan Asuransi Wajib di Indonesia Studi pada PT. Jasa Raharja (Persero) Tbk Periode 2013-2022 (Jurnal Simki Economic, 2024)
This study aims to determine the level of return on investment in the investment portfolio of PT. Jasa Raharja for the period 2013 to 2022. This research method uses a quantitative method involving the process of collecting secondary data for ten years, then conducting a financial ratio analysis followed by multiple regression analysis, then describing the interpretation of the research results. The results of the financial ratio analysis using the net investment income ratio showed that in each period the level of return on the investment portfolio tended to continue to decline from 10% in 2013 to 6.89% in 2022. The results of the normality test to test the sample obtained a normally distributed sample, then the results of the multiple regression test showed that the results of the investment portfolio and the value of the investment portfolio together affected the net investment income ratio. In this study, the company was less than optimal in managing its investment funds. Therefore, the company is less able to rely on the investment returns obtained to add new investment funds in the next period. If this happens continuously, the company in meeting funds for payment of claim expenses and other company operational expenses can only rely on premium income from customers so that the company's profits are low.